2017
DOI: 10.1007/s12035-017-0620-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Stress on the Spatial Learning and GR-PKAc-NF-κB Signaling in the Hippocampus and Cortex in Rats Following Cholinergic Depletion

Abstract: Studies have shown that the removal of the cholinergic innervation to the hippocampus induces dysfunction of the hypothalamic-pituitary-adrenocortical axis and decreases the number of glucocorticoid receptors (GRs). Subsequent studies have revealed that the loss of cholinergic input to the hippocampus reduces the expression of GRs and activates nuclear factor-kappa B (NF-κB) signaling through interactions with the cytoplasmic catalytic subunit of protein kinase A (PKAc). We examined the effects of chronic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Our results that chronic stress increases levels of ROS in the hippocampus are in agreement with previous studies. Studies have also shown that chronic stress enhances NF-κB signaling induced by cholinergic depletion in the hippocampus, thereby increasing the expression of pro-inflammatory factors (Lee et al, 2018). This is in line with our current finding that chronic stress induces NF-κB expression and promotes NF-κB translocation to the nucleus in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Our results that chronic stress increases levels of ROS in the hippocampus are in agreement with previous studies. Studies have also shown that chronic stress enhances NF-κB signaling induced by cholinergic depletion in the hippocampus, thereby increasing the expression of pro-inflammatory factors (Lee et al, 2018). This is in line with our current finding that chronic stress induces NF-κB expression and promotes NF-κB translocation to the nucleus in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, as has largely been explained in terms of excess glucocorticoid production which proposes that depression is a type of stress response involving a chronic production of glucocorticoids which implicate the hypothalamic, pituitary, and limbic systems ( Sheline, 2011 ). Several studies have shown that cumulative exposure to glucocorticoids has been related to hippocampal (i.e., a core limbic structure) volume reduction and impairments in hippocampal-dependent cognitive tasks in rodents ( Woolley et al, 1990 ; Watanabe et al, 1992 ; Lee et al, 2017 ; Nguyen et al, 2018 ). Studies in humans have shown similar findings in healthy older adults who report high levels of stress concurrent with high levels of cumulative cortisol levels ( Newcomer et al, 1999 ; Gold, 2015 ; Radley et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CRS model can also affect the immune system of animals, and studies have shown that chronic stress enhances NF-κB signaling in the hippocampus, thereby increasing the expression of pro-inflammatory factors [ 29 ]. Here, we found that the SYNS treatment groups improved the inflammatory response caused by the CRS model, and the differences between the model group and the medication groups were observed in the subsequent hippocampal pathomorphological observation, suggesting anti-inflammatory effect of SYNS to a certain degree.…”
Section: Discussionmentioning
confidence: 99%